Pengukuran Kinerja Bank Syariah: Integrasi Pendekatan DEA dengan Analisis Rasio Keuangan - R. Nugroho Purwantoro (Jurnal Manajemen dan Usahawan Indonesia, 2020)
This paper integrated DEA method with financial ratio to analyze efficiency and performance of sharia business unit at 4 Indonesian banks in 2 years period. This paper identify 4 difference performance condition in each unit that in term of asset accumulation commanding up to 71% of all Indonesian sharia banking total asset.